Do Poverty and Economic Growth Matter for Income Inequality Reduction in Yogyakarta Province? - Maurilla, Athari; Suriani, Suriani; Nasir, Muhammad (Universitas Muhammadiyah Yogyakarta, 2022)
It has been observed that income inequality is an economic element that may impede a nation's economic development. In general, Indonesia's Gini ratio has remained low for nearly a decade, although one region, Yogyakarta Province, unexpectedly exceeds the national average. The provincial government of Yogyakarta must focus more on reducing income inequality. Therefore, this study employs the Poverty-Growth-Inequality Triangle model approach to investigate the complexity of income inequality in Yogyakarta Province. The data is collected from five cities in Yogyakarta Province from 2010 to 2021. For the quantitative study, a Simultaneous Equation Model analysis with three iterations of least squares is performed. The results indicate that there is no causal relationship between income inequality and economic growth or poverty. According to the model of income inequality, education and the district minimum wage have a significant impact on income inequality. Therefore, local governments are advocated to evaluate policies aimed at reducing income inequality through education system reform, equity in district minimum wage and economic growth, and efficiency in the utilization of income inequality-related funds.